Disaster, environment and local indigenous knowledge in Indonesia - Dede Moh.; Kusumaningsih Siti Nurbayani; Widiawaty Millary Agung; Nandhita Ni Gusti Ayu; Wahyuni Sri; Khosihan Aan; Utami Nindita Fajria; Wulandari Puspita; Setiadi Elly Malihah; Ismail Arif (E3S Web of Conferences)
Indonesia is a disaster-prone area due to its complexity in geographical and geological location. For thousands of years, Indonesian society has interacted with various natural disasters. This research aims to summarize and synthesize community adaptation to various disasters by referring to their local indigenous knowledge. Data came from previous studies recorded in two most reputable scientific databases, namely Web of Science and Scopus, 1980 to 2023 . Our review used a qualitative approach with content analysis, resulting in 16 articles that were suitable for metaanalysis. This research shows that local indigenous knowledge in Indonesian society has included environmental adaptations to several disasters, such as floods, landslides, tsunamis, earthquakes, plagues, volcanic eruptions, and other hydrometeorological extreme events. Local indigenous knowledge is mostly spoken orally through various traditions, traditional houses, living equipment, poetry, regional zoning, and traditional institutions that imply disaster events, but there are no written remains. Their experience has not shown any adaptation to disaster-induced environmental changes due to climate change and global warming. Our research can provide input for disaster mitigation that is more appropriate to the local context.